A bibliometric analysis of research trends on the sustainable development of the agri-food industry and its impact on food security - Anar Abbasov; Azer Gurbanzade (Environmental Economics)
The sustainable development of the agri-food industry has become increasingly critical in the face of rising food insecurity, climate change, and recent global disruptions such as the COVID-19 pandemic and geopolitical conflicts. This study aims to perform a bibliometric analysis of global research concerning the sustainable development of the agri-food industry and its implications for food security across nations. Drawing on 1,704 Scopus-indexed publications from 1993 to the first quarter of 2025, the study identifies four distinct phases of research growth, ranging from an exploratory stage to a recent surge in interdisciplinary and technology-focused studies. Keyword co-occurrence analysis reveals five major thematic clusters: agri-food supply chains, environmental sustainability, public health and nutrition, technological and product innovation, and systemic food security. Thematic evolution demonstrates a clear progression from fragmented early research to integrated, systems-based approaches, with a growing emphasis on digital technologies (e.g., AI, blockchain, and IoT) and circular economy principles. Despite rapid thematic expansion, the study highlights ongoing gaps in connecting sustainability research to actionable food security strategies in low- and middle-income regions.